Literature Review of the Application of Total Productive Maintenance (TPM) in various industries in Indonesia - Lucky Setiawan (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2021)
This research is a literature review from various journals with the theme Total Productive Maintenance which is implemented in various companies in Indonesia. The purpose of this paper is as a means of sharing and learning between companies that can be taken as a brainstorming theme related to machine performance within a company, which may not occur between companies that problems outside of the machine problem. The OEE factor of the machine is one of the parameters that is the goal which results in poor engine performance. The research method is to search journals from various sources that have keywords related to TPM. The number of journals found from 2015 to 2020 was 60 journals which were finally iterated to become 46 journals to be selected for this paper. The concept of Pareto and Root caused Analysis (4M + E) is a helpful tool in concluding the literature review in this paper, while the TPM Pillar will provide a solution guide for each problem that has been summarized in 4M + E which will be classified from each problem to be the solution of the problem. that has been found. The conclusions of this literature review are related to this new card problem which is the focus of attention. It is the result of operator changes associated with the contract system which causes this change to be properly prepared at the time the new operator works. The previous operator's method that has been good needs to be transferred to the operator that will enter. However, this is often a big gap with the preparation of this skill transfer and the fatigue factor of operators who have side jobs, with the proliferation of online-based applications causing business operators to seek additional income so that their main work is neglected.